Pengaruh Gaya Kepemimpinan Suportif terhadap Kualitas Jasa Pelayanan Mahasiswa di Jurusan Administrasi Bisnis - Muhammad Yasin; Azwar Azwar; Fortuna Zain (Epigram, 2016)
This research aimed to know how much percentation and how the relationship between supportive leadership style against the quality of student service in Business of Administration Departement. Observation against the quality of student service in Business of Administration Departement made across survey approach by collecting data from respondents were obtained from spreading survey directly to students in student service locket. In this research, data analysis method which was used was validity and reliability test, normality test, the coefficient of determination analysis, t test, simple linear regression analysis, product moment correlation analysis. The result of the research showed that had low relationship but real impact between supportive leadership style with the quality of student service in Business of Administration Departement. Supportive Leadership style (independent variable) was researched which had relationship around 20,5% against the quality of student service in Business of Administration Departement and the rest arounded 79,5% was determined by the another factor.